Development of Learning Media for Islamic Fiqh Educational Games on Learning Interest - Amrini Shofiyani; Mar'atush Sholihah (SCHOOLAR: Social and Literature Study in Education, 2021)
The advancement of science and information and communication technology as a product of changing times has had a positive impact on the advancement of today's education world. The era of digitalization, which is called the era of the industrial revolution 4.0, is making very rapid changes. There are many digital learning applications that can be used effectively and efficiently as a medium for supporting learning, this research requires innovation in learning media so that students don't feel bored when learning and teaching. There are many digital learning applications that can be used effectively and efficiently as learning support media, including word wall games. This research is a development on the use of learning media for word wall educational games on the interest in learning fiqh in class viii students at MTs AL-IHSAN Banjaragung in the academic year 2020/2021. The purpose of this study is to determine the increase in student interest in learning. This type of research is development research (R&D). To produce a product and test the effectiveness of the product using Sugiono's theory by using the first few stages of planning with identification of the problem potential, the second stage is making a new design, the third stage is validating the design, the fourth stage is design revision, the fifth stage is validating the design, and the sixth stage is testing the product. The results of this study indicate that the use of word wall media in fiqh learning has been proven to increase students' interest in learning and activeness in learning fiqh.